(untitled) (International Journal of Scientific Pediatrics, 2023)
Abstract: This review article discusses the role of micro and macro elements in pediatrics. A thorough study of the biological role of MEs, carried out in recent years, has made it possible to accumulate factual material reflecting their influence on various physiological functions of the body and, in particular, on the metabolism of a growing organism. About 20 chemical elements take part in the formation and development of various body tissues and their physiological reactions. MEs take an active part in various types of metabolism of proteins, fats, and carbohydrates; influence the course of redox processes, the synthesis of hormones, the functions of the internal secretion organs and the nervous system. The effects of ME, which are part of physiologically active compounds, manifest themselves mainly in their influence on metabolic processes and their too high or too low content is fraught with far-reaching consequences. Knowledge of the physiological level of vitally important, irreplaceable MEs in the body of newborns, the parameters of their balance and significance in the processes of adaptation to extrauterine living conditions will contribute to the development of measures to prevent the implementation of maladaptive syndromes and those diseases in the genesis of which the main role is played by a lack or excess of MEs in the body, their imbalance.